Ligand-induced amorphous and dense interface formation in bone char/Fe(OH)2 hybrid suspension to enhance FeN mediated TCE dehalogenation - Yanhui Yi; Aihua Wei; Pingping Chen; Ning Wang; Jinxin Zhao; Weizhao Yin (Chemical Engineering Journal, 2026)

Improving sodium polysulfide transformation through dual-anchoring mechanism with V2C MXene - Xiaoyu Zhang; Zhiyu Fang; Luzhou Zhang; Pingping Zhou; Renyu Chang; Xuanming Chang; Liang Zhang; Ning Lu; Hengxing Ji; Zhen Fang (Chemical Engineering Journal, 2026)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

PI3KR1 and AKT1 in largemouth bass (Micropterus salmoides): molecular cloning, characterization, and its involvement in the alleviation of hepatic glycogen deposition caused by insulin inclusion in vitro - Yuru Li; Shiwen Chen; Yijun Liu; Pingping Liu; Songlin Li; Ning Liu (Fish Physiology and Biochemistry, 2024)

Metagenomic and isotopic insights into carbon fixation by autotrophic microorganisms in a petroleum hydrocarbon impacted red clay aquifer - Zhuo Ning; Yizhi Sheng; Shuang Gan; Caijuan Guo; Shuaiwei Wang; Pingping Cai; Min Zhang (Environmental Pollution, 2024)

Metagenomic analysis revealed highly diverse carbon fixation microorganisms in a petroleum-hydrocarbon-contaminated aquifer - Zhuo Ning; Pingping Cai; Min Zhang (Environmental Research, 2024)

Exploring the association between air pollution and Parkinson’s disease or Alzheimer’s disease: a Mendelian randomization study - Pingping Ning; Xingzhi Guo; Qiumin Qu; Rui Li (Environmental Science and Pollution Research, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Bacterial wilt suppressive composts: Significance of rhizosphere microbiome - Jia Ding; Ning Wang; Pingping Liu; Baoju Liu; Yuelin Zhu; Jing Mao; Yue Wang; Xiaoyan Ding; Hefa Yang; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

Prenatal diagnosis of the Dandy–Walker malformation associated with partial trisomy 12p and distal 15q deletion - Yanmei Sun; Ning Zhang; Haishen Tian; Pingping Zhang; Yali Li (Journal of Genetics, 2021)

LRP10 Mutations May Correlate with Sporadic Parkinson’s Disease in China - Quanzhen Zhao; Pingping Ning; Xinglong Yang; Changhe Shi; Yuming Xu; Qiuyan Shen; Hongyan Huang; Dan Xie; Yalan Chen; Yanming Xu (Molecular Neurobiology, 2021)

Extracellular production of recombinant N-glycosylated anti-VEGFR2 monobody in leaky Escherichia coli strain - Ning Ding; Xin Fu; Yao Ruan; Jing Zhu; Pingping Guo; Lichi Han; Jianing Zhang; Xuejun Hu (Biotechnology Letters, 2019)

Reactive oxygen species induced by personal exposure to fine particulate matter emitted from solid fuel combustion in rural Guanzhong Basin, northwestern China - Yaqi Li; Hongmei Xu; Kailai He; Jinhui Wang; Zhi Ning; Qiyuan Wang; Nan Li; Zhenxing Shen; Pingping Liu; Jian Sun; Xinyi Niu; Yongxiao Cao; et al. (Air Quality, Atmosphere & Health, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Photocatalytical Deactivation of Pathogens for Municipal Wastewater Reusing - Hongbo Wang; Pingping Jia; Ning Ding; Guori Pang; Ning Wang (Water, Air, & Soil Pollution, 2015)

Soil fertility and its significance to crop productivity and sustainability in typical agroecosystem: a summary of long-term fertilizer experiments in China - Qingyin Shang; Ning Ling; Xumeng Feng; Xiuxia Yang; Pingping Wu; Jianwen Zou; Qirong Shen; Shiwei Guo (Plant and Soil, 2014)

Ammonia volatilization in Chinese double rice-cropping systems: a 3-year field measurement in long-term fertilizer experiments - Qingyin Shang; Cuimin Gao; Xiuxia Yang; Pingping Wu; Ning Ling; Qirong Shen; Shiwei Guo (Biology and Fertility of Soils, 2014)

Some observations on harmful algal bloom (HAB) events along the coast of Guangdong, southern China in 1998 - Yuzao Qi; Jufang Chen; Zhaohui Wang; Ning Xu; Yan Wang; Pingping Shen; Songhui Lu; I.J. Hodgkiss (Hydrobiologia, 2004)